Code-mixing Types and Reasons among Instagram Users - Inggraini Hartono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aimed to identify the types of code-mixing among Instagram users who are closed and followed by the researcher and the reasons of using it on Instagram. This research will apply descriptive qualitative research design. The participants are the Instagram feed with posts from those who are connected to the researcher. From one thousand eight hundred ninety-four Instagram users, there are twenty-three Instagram feeds who are notified using code mix in their feed from 14 December 2020 to 8 January 2021. Using the three types of code-mixing from Hoffmann (1991) and the seven reasons for bilinguals proposed by Hoffmann (1991) the data was collected using observation and interview. Based on the observation, twenty-one (21) intra-sentential code-mixing which was about ninety-one percent, two (2) intra-lexical code-mixing, and seven (7) a change of pronunciation mixing were found in the researcher’s friends Instagram feeds. From the interview, most of the reasons was talking about a particular topic because they feel comfortable and cannot think of the other word in the Indonesian language. The words such as: “field trip”, “online school”, “viral”, “update”, “share” are the common words they find in society and they cannot find the Indonesian words for them.